Earnings Management: The Misapplication Of Accounting Rules And Standards. - DBA, Kingsley Wokukwu (Archives of Business Research, 2019)
This paper discuses earnings management and also explores the role accounting standard played. The plethora of financial scandal and earnings restatements in recent years has left many investors questioning whether reported earnings can ever be free of earnings management, earnings manipulation, earnings smoothing and restatements. The paper looks at the role auditors and other external factors play in earnings management and revenue recognition. The paper finds that some of the improprieties relating to earnings management stems from an outdated accounting standards, complex corporate financing arrangements, preservation of executive compensation incentives and corporate pressure to meet earnings projections.